ANALYSING AND IMPROVING THE DYNAMICS OF SEWING MACHINE FABRIC FEED MECHANISMS - Palvannazirova Nasiba; Assistant Professor Butovskiy P.M. (Scholar Express Journal, 2024)
The article examines how sewing machine fabric transportation mechanisms work and the factors that affect their quality. It also analyses the design factors that determine their dynamic performance and suggests ways to improve their design for better dynamic characteristics and increased reliability.
Keywords: sewing machine; fabric transportation; dynamics